2009
DOI: 10.1152/jn.90991.2008
|View full text |Cite
|
Sign up to set email alerts
|

GABAA Receptors Containing Gamma1 Subunits Contribute to Inhibitory Transmission in the Central Amygdala

Abstract: Esmaeili A, Lynch JW, Sah P. GABA A receptors containing gamma1 subunits contribute to inhibitory transmission in the central amygdale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 35 publications
4
35
0
Order By: Relevance
“…Experiments using flunitrazepam and diazepam demonstrate that benzodiazepines are ineffective at enhancing synaptic currents mediated by ␥1-containing GABA A Rs. This result is consistent with whole cell peak current measurements of ␥1-containing GABA A Rs (18), and key differences in the amino acid sequence between ␥2L and ␥1 that have been shown to affect the potency with which benzodiazepine-site ligands modulate currents (49 -52).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Experiments using flunitrazepam and diazepam demonstrate that benzodiazepines are ineffective at enhancing synaptic currents mediated by ␥1-containing GABA A Rs. This result is consistent with whole cell peak current measurements of ␥1-containing GABA A Rs (18), and key differences in the amino acid sequence between ␥2L and ␥1 that have been shown to affect the potency with which benzodiazepine-site ligands modulate currents (49 -52).…”
Section: Discussionsupporting
confidence: 86%
“…␥1-Containing GABA A Rs Are Insensitive to Benzodiazepine Current Enhancement-Because ␥1-containing receptors have been reported to be less sensitive to benzodiazepine drugs (18,19,21), we compared the actions of flunitrazepam and diazepam on IPSCs from cells expressing either ␣2␤2␥1 or ␣2␤2␥2L receptors. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the GABA A synaptic current, t 1 ¼ 0.8 msec, t 2 ¼ 13 msec for ITC cells (Geracitano et al 2007), and t 1 ¼ 0.8 msec, t 2 ¼ 40 msec for Ce neurons (Esmaeili et al 2009). The maximal conductances were chosen as: g AMPA, max ¼ 1 nS, g NMDA, max ¼ 0.5 nS (Li et al 2009), and g GABAA, max ¼ 0.6 nS (Geracitano et al 2007).…”
Section: Synaptic Currentsmentioning
confidence: 99%
“…This agrees with previous studies that demonstrated that γ subunits confer zinc insensitivity to αβ GABA A Rs. 10,12 To distinguish the pharmacological properties of α1β1γ1 and α1β1γ2 GABA A Rs, we investigated the effects of DMcM and zolpidem, both of which discriminate strongly between γ1-and γ2-containing receptors. DMcM potently inhibits γ2-containing GABA A Rs but has either no effect on or modestly potentiates γ1-containing GABA A Rs.…”
Section: Pharmacology Of γ Subunit-containing Receptorsmentioning
confidence: 99%